STUDENT PERFORMANCE AND COURSE EVALUATIONS BEFORE AND AFTER USE OF THE CLASSROOM PERFORMANCE SYSTEM™ IN A THIRD‐YEAR VETERINARY RADIOLOGY COURSE. Issue 2 (12th December 2012) - Hecht, Silke; Adams, W. H.; Cunningham, M. A.; Lane, I. F.; Howell, N. E.
<x xml:space="preserve">Abstract</x> Effective teaching of veterinary radiology can be challenging in a traditional classroom environment. Audience response systems, colloquially known as "clickers, " provide a means of encouraging student interaction. The purpose of this study was to compare student performance and course evaluations before and after using the Classroom Performance System™ in the third‐year (fifth semester) didactic radiology course at the University of Tennessee College of Veterinary Medicine. Overall student performance was assessed by comparing median numeric final course grades (%) between years without and with use of the Classroom Performance System™. Grades of students were determined for individual instructors' sections. Student evaluations of the radiology course were compared for the years available (2007–2010). Student interactions were also evaluated subjectively by instructors who used the Classroom Performance System™. There was a significant difference (p = 0.009) between the median student grade before (2005 – 2008, median 82.2%; interquartile range 77.6–85.7%; range 61.9–95.5%) and after use of the classroom performance system (2009–2010, median 83.6%; interquartile range 79.9–87.9%; range 68.2–93.2%). There was no statistically significant difference in median student grades for individual instructors over the study period. The radiology course student evaluation scores were significantly higher in years where the Classroom Performance System™ was used in comparison to previous years (P = 0.019). Subjectively, students appeared more involved when using clickers. Findings indicated that the Classroom Performance System™ may be a useful tool for enhancing veterinary radiology education.